Analisis Perbandingan Kinerja Keuangan Perusahaan Akuisitor Sebelum dan Sesudah Merger & Akuisisi (M&A) Tahun 2015 - Unun Khoirun Nisak (Jurnal Ilmu Manajemen, 2020)
The purpose of this study is to analyze differences in the financial performance of acquisitor companies before and after mergers & acquisitions (M&A) in 2015. Financial performance measurement tools are Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), Total Assets Turnover (TATO), and Market Value Added (MVA). The observation period is for 3 years before and after mergers & acquisitions. The sampling technique that is purposive sampling was obtained by 4 companies of acquisitor. Data analysis techniques used Wilcoxon signed-rank t-test and paired sample t-test. The results of this study are that there is no difference in CR and DER but there are differences in ROE, TATO, MVA in the acquisition company 3 years before and after M&A. The overall results are concluded that the financial performance of the acquisition companies after M&A decreased so that the synergy expected by the company was not achieved.